2015
DOI: 10.1016/j.funbio.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the community diversity of foliar fungal endophytes between seedling and adult loblolly pines (Pinus taeda)

Abstract: Fungal endophytes represent one of the most ubiquitous plant symbionts on Earth and are phylogenetically diverse. The structure and diversity of endophyte communities have been shown to depend on host taxa and climate, but there have been relatively few studies exploring endophyte communities throughout host maturity. We compared foliar fungal endophyte communities between seedlings and adult trees of loblolly pines (Pinus taeda) at the same seasons and locations by culturing and culture-independent methods. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 75 publications
8
60
2
5
Order By: Relevance
“…Green needles were washed and surface‐sterilized as described in Oono et al. (2015). Green needles were cut with a sterile razor blade into 2‐mm‐long sections.…”
Section: Methodsmentioning
confidence: 99%
“…Green needles were washed and surface‐sterilized as described in Oono et al. (2015). Green needles were cut with a sterile razor blade into 2‐mm‐long sections.…”
Section: Methodsmentioning
confidence: 99%
“…Similar conclusions were made by Langarica-Fuentes et al (2014) who identified a biased composition of compost fungi by cultivation. Recently, HTS was rated superior over cultivation, given its ability to detect more obligate, slow growing and rare fungi (Al-Sadi et al 2015, Oono et al 2015. Whereas the general lack of congruence between mycobiomes generated by cultivation and HTS can be safely postulated nowadays (Pitkaranta et al 2008), much less is known about environmental correlations of these differing data sets.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal endophytes are ubiquitous, they have been found within all plants from the diverse habitats examined to date (Kumaresan & Suryanarayanan 2001;Schulz et al 2002;Rodriguez et al 2009;Pancher et al 2012). The endophytic community in a single plant is usually composed by numerous and systematically diverse species of fungi (Petrini 1991;Oono et al 2015). Their number and species composition is influenced by factors such as the environment (Saona et al 2010;Yousaf et al 2010;N unez-Trujillo et al 2012), plant physiology (Islam et al 2010), anthropogenic factors (Rasche et al 2006), and pathogen infections (Araujo et al 2002;Bulgari et al 2011;Buyer et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Endophytes have been gaining attention in the past decade in areas such as medicine, agriculture, and industry, mostly due to the vast potential uses of their chemically diverse secondary metabolites (Tao et al 2008;Rodriguez et al 2009) and their roles within plants (Oono et al 2015). Several studies have shown that some fungal endophytes have beneficial effects on their hosts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation